2021
DOI: 10.1088/1402-4896/ac1f5d
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase pressure drop analysis of swirl tube in one-side high heat load condition for plasma facing component application

Abstract: In this study, the two-phase pressure drop of a one-side heated swirl tube (twist ratio=3, 5) was experimentally studied. If the a heat flux is gradually increased, the vapor blocks the flow path, thus leading to an increase in the differential pressure. As the inset sub-cooling and mass flow rate increase, the vapor is removed by condensation more rapidly, and thus, the rate of increase of differential pressure is reduced. From the evaluation of the prediction performance of the existing two-phase pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Therefore, in this part, by cooling the amount of heat loaded in the test-section, the thermal steady state can be maintained in the closed loop. Further details on the selection of experimental equipment and design of the experimental loop can be found in our previous studies [23][24][25][26], and the experimental range of and the uncertainty of the measured variables in this study can be found in table 2.…”
Section: Experimental Methods 21 Experimental Loopmentioning
confidence: 99%
“…Therefore, in this part, by cooling the amount of heat loaded in the test-section, the thermal steady state can be maintained in the closed loop. Further details on the selection of experimental equipment and design of the experimental loop can be found in our previous studies [23][24][25][26], and the experimental range of and the uncertainty of the measured variables in this study can be found in table 2.…”
Section: Experimental Methods 21 Experimental Loopmentioning
confidence: 99%
“…This series of processes creates a secondary flow on the wall and promotes heat transfer. Bowring [7] named the secondary flow effect due to the accelerated bubble departure frequency and the collapse of the thermal boundary layer in the FDB regime as agitation heat flux. He derived the equation for the agitation heat flux at the wall, as shown in equation (3) under the assumption that the volume of the bulk fluid flowing into the wall can be treated as a slug equal to the volume of the departed bubble, where N a denotes the active nucleation site density, f the bubble departure frequency, and V b the volume when the bubble departs.…”
Section: Flat Heat Sink Test Sectionmentioning
confidence: 99%
“…In particular, the vertical targets of the divertor, which removes helium ash and facilitates plasma operation, are loaded with an ultra-high heat flux of up to 20 MW m −2 [5]. If such a large energy is transferred to the fluid inside the channel, severe boiling phenomenon occurs, the differential pressure increases [6], and there is a risk of inducing flow instability [7]. However, among the engineering issues caused by the one-side high heat load condition, the concentration of heat flux at the top of the cooling channel can not only lower the critical heat flux, which is the maximum heat flux that the cooling channel can withstand, but also cause material damage such as cracks [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of cooling channel structures that can withstand ultrahigh temperatures have been proposed as candidate solutions. The most representative channel structures are the swirl tube [8], hypervapotron channel [9], and screw tube. Screw tubes contain cooling channels with helical nut structures on the flow path wall, providing excellent cooling performance and critical heat flux (CHF) performance through the generation of secondary flow near the flow path wall [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous thermo-hydraulic performance evaluation studies of screw tubes assessed CHF performance to determine whether the tube could withstand the ultra-high heat flux within a tokamak. However, the cooling system of a power plant operating under subcooled flow conditions is designed to function in an SP regime, as the vapor produced within a channel under a two-phase regime is a potential hazard in terms of flow instability [18], increased two-phase pressure drop [8,10], and CHF. Figure 2 shows the three flow regimes that occur inside a channel under the subcooled flow boiling and one-side heating conditions.…”
Section: Introductionmentioning
confidence: 99%